2008
DOI: 10.1002/ldr.861
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fencing, artificial seeding and abandonment on vegetation composition and dynamics of ‘black soil land’ in the headwaters of the Yangtze and the Yellow Rivers of the Qinghai‐Tibetan Plateau

Abstract: Rangeland management can affect plant diversity and plant functional groups of native grassland communities. To improve pasture for livestock grazing from the existing poisonous and ruderal vegetation in the 'black soil land' grassland in the headwaters of the Yangtze and the Yellow Rivers (HAYYR) of the Qinghai-Tibetan Plateau, three treatments (fencing-FT, artificial seeding with local grasses-ST and abandonment-AT) were applied during a 5-year period (2000)(2001)(2002)(2003)(2004)(2005). Plant diversity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 20 publications
8
89
0
Order By: Relevance
“…The findings reveal a possible trade-off between carbon sequestration and diversity maintenance in China's grasslands. Therefore, we proposed that short-term grazing exclusion is essential and important for restoring degraded grasslands (Su et al, 2005;Shang et al, 2008;Liu et al, 2014). Longterm grazing exclusion may not be a good management option according to our results, for the following reasons.…”
Section: Implications For Sustainable Grassland Management Strategiesmentioning
confidence: 83%
See 2 more Smart Citations
“…The findings reveal a possible trade-off between carbon sequestration and diversity maintenance in China's grasslands. Therefore, we proposed that short-term grazing exclusion is essential and important for restoring degraded grasslands (Su et al, 2005;Shang et al, 2008;Liu et al, 2014). Longterm grazing exclusion may not be a good management option according to our results, for the following reasons.…”
Section: Implications For Sustainable Grassland Management Strategiesmentioning
confidence: 83%
“…Excessive grazing and trampling by domestic animals may inhibit plant reproduction and regeneration, and resulting in the loss of some associated species in overgrazed grasslands (Sternberg et al, 2000;Firincioglu et al, 2007). Therefore, removing grazing pressure would facilitate the growth of suppressed species and increase species richness at the early stage of grazing exclusion (Luno et al, 1997;Shang et al, 2008). However, along with vegetation succession proceeding, the long-term absence of disturbance led to the preponderance of dominant species over time.…”
Section: Effects Of Grazing Exclusion On Plant Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that heavily and severely degraded grassland (called the "black beach") represented approximately 34 and 8 %, respectively, of the grassland area in the headwaters region (Ma et al 2006;Shang et al 2008;Wang et al 2009). Despite numerous efforts to protect the grassland resource in this area, grassland degradation is continuing due to overgrazing, overexploitation of medicinal plants, destruction by rodents, and climatic warming and drought (Zhou et al 2005;Wang and Fu 2004;Gao et al 2009;Feng et al 2010;Wang et al 2008Wang et al , 2011bLi et al 2011a, b;Xu et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Frequently, researchers have described pastures according to the extent to which they have become degraded, such as slightly, moderately, severely, or extremely degraded (Liu et al 2004b;Yuan and Zhou 2004;Zhou et al 2005;Ma 2007;Liu and Dong 2008), in order to ascribe restorative programs appropriate to the degree of degradation (Shang et al 2013), and an overall reduction in herbage mass and feeding value of herbage (Shang and Long 2007;Shang et al 2008Shang et al , 2013Gao et al , 2010Li et al 2013aLi et al , 2013bWen et al 2013). With changes in species composition, sward structure deteriorates and areas of bare soil increase, leading eventually to loss of soil structure and the possibility of soil erosion, all of which creates considerable challenges for grassland restoration .…”
Section: Restoration Of Degraded Grassland (A)mentioning
confidence: 99%